Membangun Pemasaran Digital pada UMKM Raja Souvenir di Kecamatan Adiwerna - Galih Widyatmojo; Muhammad Wildan Agustri; Nur Fajri Maulana (JURPIKAT, 2026)
Raja Souvenir MSME in Adiwerna District faces a significant revenue decline due to dependence on conventional marketing and weak digital visual identity. This Community Service (PKM) activity aims to build an integrated digital marketing ecosystem to expand market reach. The implementation method followed systematic stages including field observations, in-depth interviews, and independent digital infrastructure implementation to ensure uninterrupted partner production. Results encompass ten primary outputs, notably visual identity redesign (logo), official catalog website development (shoprajasouvenir.my.id), Google Maps optimization, and a Manual Book certified with Intellectual Property Rights (IPR). The integration of this digital infrastructure successfully enhanced online visibility, business credibility, and partner independence in managing marketing within a sustainable digital ecosystem. This project is documented in an accredited national journal as a scientific contribution to local MSME development.